Strength, durability, and economic analysis of GGBS-based geopolymer concrete with silica fume under harsh conditions - Sagar Paruthi; Ibadur Rahman; Afzal Husain Khan; Neha Sharma; Ahmad Alyaseen (Scientific Reports)
Abstract Geopolymer concrete (GPC) offers a sustainable alternative by eliminating the need for cement, thereby reducing carbon dioxide emissions. Using durable concrete helps prevent the corrosion of reinforcing bars and reduces spalling caused by chemical attacks. This study investigates the impact of adding 5, 10, and 15% silica fumes (SF) on the mechanical and durability properties of GPC cured at 60 °C for 24 h. In the research, concrete specimens were submerged continuously for 62 days in four different chemicals: 6% sodium sulfate, 6% sodium chloride, 2% sulfuric acid, and 2% hydrochloric acid. The study assessed the effects of chemical exposure on concrete properties by examining water absorption, sorptivity, and compressive strength loss in GPC specimens. Maximum compressive strength, split tensile strength, and flexural strength of about 48.35 MPa, 4.91 MPa, and 5.01 MPa are achieved after incorporation of 10% SF in GPC after 28 days of curing. Results indicated that GPC with a significant dosage of SF (10%) improves its mechanical and durability properties. The maximum rebound number and ultrasonic pulse velocity are achieved after 90 days of curing with a 10% dosage of SF. Moreover, an economic analysis was conducted to confirm the economic viability.